CleanEMG: Comparing Interpolation Strategies for Power Line Interference Quantification in Surface EMG Signals - Abser, Nurul; MacIsaac, Dawn; Chan, Adrian D. C.; Fraser, Graham; Green, James R. (CMBES Proceedings, 2012)
Quantifying 50/60Hz power line interference in surface electromyography through spectral interpolation is investigated. The quantification method is based on interpolating the signal spectrum about its 50/60Hz components to estimate the signal, and then the power line interference. Once these constituents are differentiated, a signal-to-60Hz-Noise ratio may be estimated and used as a quantifying metric. Simulations were used to compare estimation error introduced by two interpolation methods, one using the raw spectrum, and another using a smoothed spectrum. Results indicate that the smoothed spectrum method performs moderately better, but both can yield estimation errors <10% relative to signal power.